YHSeqY3000 panel captures all founding lineages in the Chinese paternal genomic diversity database - Mengge Wang; Shuhan Duan; Qiuxia Sun; Kaijun Liu; Yan Liu; Zhiyong Wang; Xiangping Li; Lanhai Wei; Yunhui Liu; Shengjie Nie; Kun Zhou; 10K_CPGDP consortium; et al. (BMC Biology)
Abstract Background The advancements in second-/third-generation sequencing technologies, alongside computational innovations, have significantly enhanced our understanding of the genomic structure of Y-chromosomes and their unique phylogenetic characteristics. These researches, despite the challenges posed by the lack of population-scale genomic databases, have the potential to revolutionize our approach to high-resolution, population-specific Y-chromosome panels and databases for anthropological and forensic applications. Objectives This study aimed to develop the highest-resolution Y-targeted sequencing panel, utilizing time-stamped, core phylogenetic informative mutations identified from high-coverage sequences in the YanHuang cohort. This panel is intended to provide a new tool for forensic complex pedigree search and paternal biogeographical ancestry inference, as well as explore the general patterns of the fine-scale paternal evolutionary history of ethnolinguistically diverse Chinese populations. Results The sequencing performance of the East Asian-specific Y-chromosomal panel, including 2999-core SNP variants, was found to be robust and reliable. The YHSeqY3000 panel was designed to capture the genetic diversity of Chinese paternal lineages from 3500 years ago, identifying 408 terminal lineages in 2097 individuals across 41 genetically and geographically distinct populations. We identified a fine-scale paternal substructure that was correlating with ancient population migrations and expansions. New evidence was provided for extensive gene flow events between minority ethnic groups and Han Chinese people, based on the integrative Chinese Paternal Genomic Diversity Database. Conclusions This work successfully integrated Y-chromosome-related basic genomic science with forensic and anthropological translational applications, emphasizing the necessity of comprehensively characterizing Y-chromosome genomic diversity from genomically under-representative populations. This is particularly important in the second phase of our population-specific medical or anthropological genomic cohorts, where dense sampling strategies are employed.